DEVELOPMENT OF STUDENTS WORKSHEET WITH MIND MAPPING STRATEGY TO IMPROVE THE STUDENTS CREATIVE THINKING SKILLS ON STOICIOMETRY MATERIALS - Hikma Wardani; Mitarlis Mitarlis (JCER (Journal of Chemistry Education Research), 2019)
The learning process of 2013 curriculum emphasizes on the students skill, it also demands them to be more active and have extraordinary abilities such as creative thinking skills. The purpose of this study is to describe the feasibility of the Students Worksheet with the mind mapping strategy to improve the students creative thinking skills on stoichiometry material. There are tree aspects which were observed in the students worksheets to measure the feasibility, those are content, presentation, and language. This study was conducted based on 4-D development model which has been modified into 3-D (define, design, and develop). The limited trial was implemented on 12 students of X Science 2 in Senior High School 3 Mojokerto. Furthermore, the results showed that from the three aspects of students worksheet which were content, presentation and language were categorized to be very feasible with the percentage 91.88%;93.55%;86.67 % . The students activities and responses were the data that obtained through the limited trials with the percentage 97.62% and 88.02% of each. Moreover, the increasing of the students creative thinking skills and learning outcomes can be seen from the N-Gain value which were 0.74 and 0.75, and belonged to high category. Based on the results it can be concluded that the students worksheet with a mind mapping strategy was feasible and able to improve the students creative thinking skills and learning outcomes on stoichiometry material